(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of vowel modifications in connected speech, focusing on processes like vowel reduction, elision, coalescence, glide formation, and changes between diphthongs and monophthongs. It explains how these modifications enhance fluency and efficiency in spoken language while preserving intelligibility. The discussion highlights the interplay between phonetics, linguistic structure, and social context, emphasizing the universality and variability of these processes across languages and dialects. The conclusions underscore the importance of understanding vowel modifications for linguists, language learners, and anyone interested in the dynamics of natural speech. This resource is valuable for studying phonetics, sociolinguistics, and secondlanguage acquisition.